2010
DOI: 10.1074/jbc.m109.059055
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Up-regulates Atoh1 Expression in Neural Progenitor Cells by Interaction with an Atoh1 3′ Enhancer

Abstract: Atoh1, a basic helix-loop-helix transcription factor, plays a critical role in the differentiation of several epithelial and neural cell types. We found that ␤-catenin, the key mediator of the canonical Wnt pathway, increased expression of Atoh1 in mouse neuroblastoma cells and neural progenitor cells, and baseline Atoh1 expression was decreased by siRNA directed at ␤-catenin. The up-regulation of Atoh1 was caused by an interaction of ␤-catenin with the Atoh1 enhancer that could be demonstrated by chromatin im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 36 publications
3
109
0
Order By: Relevance
“…Interestingly, Lgr5-EGFP expression rapidly disappears in hair cells and a subset of supporting cells. The notion that Wnt signaling plays a role in cell fate determination in the inner ear is supported by two previous studies: overexpression of ß-catenin, the central player of the canonical Wnt pathway, upregulates Atoh1 (Shi et al 2010) and induces ectopic sensory patches (Stevens et al 2003). While our data indicate that Lgr5 is not required for cochlear development, its expression likely reflects the pattern of Wnt-activated cells within the cochlear ductal epithelium.…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, Lgr5-EGFP expression rapidly disappears in hair cells and a subset of supporting cells. The notion that Wnt signaling plays a role in cell fate determination in the inner ear is supported by two previous studies: overexpression of ß-catenin, the central player of the canonical Wnt pathway, upregulates Atoh1 (Shi et al 2010) and induces ectopic sensory patches (Stevens et al 2003). While our data indicate that Lgr5 is not required for cochlear development, its expression likely reflects the pattern of Wnt-activated cells within the cochlear ductal epithelium.…”
Section: Discussionsupporting
confidence: 57%
“…Notchmediated lateral inhibition (Daudet and Lewis, 2005;Lanford et al, 1999) and innate Wnt signaling are both crucial for the development of HCs (Shi et al, 2013. The Wnt pathway interacts with the Notch pathway in development (Collu et al, 2014;Shi et al, 2010) and this interaction could regulate the level of expression of Atoh1 and other genes. Bypassing key components of developmental pathways via viral Atoh1 transduction might disrupt mechanisms that control levels of Wnt and Notch factors and thus create 'primordial' HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins have been identified that directly interact with an Atoh1 enhancer as demonstrated by chromatin immunoprecipitation, electrophoretic mobility shift assays, or luciferase activity, for example, Zic1, cdx2, Hfn1a, β-catenin, and Hic1 (Akazawa et al 1995;Ebert et al 2003;Mutoh et al 2006;Briggs et al 2008;D'Angelo et al 2010;Shi et al 2010). Atoh1, Sox2, β-catenin, Hfn1a, and Cdx2 upregulate Atoh1 expression (Helms et al 2000;Ebert et al 2003;Gazit et al 2004;Mutoh et al 2006;D'Angelo et al 2010;Shi et al 2010;Neves et al 2011). Hes1, Hes5, Sox2, Hic1, Ngn1, NeuroD1, and Zic1 repress Atoh1 at the level of transcription (Akazawa et al 1995;Gowan et al 2001;Ebert et al 2003;Qian et al 2006;Briggs et al 2008;Dabdoub et al 2008;Pan et al 2009;Jahan et al 2010).…”
Section: Genetic Regulationmentioning
confidence: 99%